2014
DOI: 10.1515/polyeng-2014-0082
|View full text |Cite
|
Sign up to set email alerts
|

Polymerization of 1,3-butadiene with neodymium chloride tripentanolate/triisobutylaluminum binary catalyst system: effect of aging time and reaction temperature

Abstract: 1,3-Butadiene monomer was polymerized at 40°C and 60°C by means of a catalyst comprising neodymium (Nd) chloride/1-pentanolate/triisobutylaluminum (TIBA) in cyclohexane as solvent; the catalyst system was aged at 5 and 30 min. The effects on conversion, catalytic activity and polymer final properties were evaluated. The obtained polybutadienes (PBs) were characterized by size exclusion chromatography (SEC), nuclear magnetic resonance (NMR) and differential scanning calorimetry (DSC) techniques and the results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 22 publications
(34 reference statements)
0
4
0
Order By: Relevance
“…At the moment we do not have an explanation for these results. Nevertheless, this behaviour is contrary to that reported for polybutadiene, where higher values of cis ‐1,4 lead to lower values of glass transition temperatures . Tables and 4 show the solution viscosity of several polymyrcenes.…”
Section: Resultsmentioning
confidence: 64%
See 1 more Smart Citation
“…At the moment we do not have an explanation for these results. Nevertheless, this behaviour is contrary to that reported for polybutadiene, where higher values of cis ‐1,4 lead to lower values of glass transition temperatures . Tables and 4 show the solution viscosity of several polymyrcenes.…”
Section: Resultsmentioning
confidence: 64%
“…As previously mentioned, different kinds of catalyst systems based on neodymium, lutetium, or lanthanum have been reported for this purpose. Recently, our research group has worked with several kinds of catalysts based on zirconium and titanium to polymerize ethylene, but mainly neodymium to polymerize 1,3‐butadiene . Different purposes drove those works; nonetheless all of them evaluated different types of alkylaluminums and/or boron compounds as catalyst activators.…”
Section: Introductionmentioning
confidence: 99%
“…The successful coordination polymerization of My, Fa, and Oc has been recently reported based on the catalytic systems widely used for f butadiene or isoprene monomers. 52,53 As one of the early reports, in 2012, Loughmari et al reported the highly selective coordination polymerization of My using neodymium borohydride/tetrahydrofuran as the catalyst and n -butylethyl magnesium as the co-catalyst. They reported polymer structures rich in 3,4 isomer and others with a high content of the cis -1,4 isomer (depending on the molar ratio of the reactants used).…”
Section: Types Of Bioelastomers and Their Synthetic Pathwaysmentioning
confidence: 99%
“…It is clearly seen that the typical melting endotherm peak of a high cis-PB gradually appears as the PS content decreases. This suggests that the PS produced is incorporated into the backbone of PB, which in large amounts seems to have the ability to inhibit the development of typical crystal structures in high cis-1,4 PB [24]. However, as the amount of PS decreases the material begins to exhibit two melting endotherms which are associated with polymorphism (capability of a rubber to crystallize in more than one crystallographic form).…”
Section: Effect Of [Al]/[nd] and [Cl]/[nd]mentioning
confidence: 99%